Long-Term Dynamic Monitoring of Post-Tensioning External Tendons: Temperature Effect Evaluation - Luis Chillitupa-Palomino; Carlos M. C. Renedo; Jaime H. García-Palacios; Iván M. Díaz (Buildings)
Cables and tendons are crucial elements in bridge engineering but also are vulnerable structural elements because they are usually subjected to fatigue and corrosion problems. Thus, vibration-based non-destructive techniques have been used for external post-tensioning tendon assessment. Regarding continuous monitoring systems, tendon assessment is carried out through the continuous tracking of its natural frequencies and the subsequent estimation of the tension force, as this parameter is essential for the bridge’s overall structural performance, thus providing useful information about bridge safety. However, for long-term monitoring assessment, two main challenges have to be addressed regarding practical applications: (i) double-peak spectra and other spurious factors that affect the frequency estimation, and (ii) temperature dependency, which needs to be carefully treated since frequency/tension variation may be explained by temperature variation, thus masking potential structural anomalies. On this subject, this paper presents the experimental long-term monitoring of several post-tensioning external tendons in a high-speed railway bridge in which a sectorized weighted peak-picking frequency identification procedure is proposed for frequency estimation, alongside a cascade clustering process, which allows meaningful frequency estimates to be selected. Finally, the selected frequency estimates, which show variations from 1 to 2% for all analyzed frequencies, are used for the long-term assessment of the tension force.